Impact of Application Programming Interfaces (APIs) Economy on Digital Economics in Saudi Arabia - Ali, Mohamed Ali; Salih, Sara Mohamed (Sustainability, 2025)
Using a panel Autoregressive Distributed Lag (ARDL) model, this study examines the effects of the adoption of Application Programming Interfaces (APIs) on the digital economy of Saudi Arabia, using monthly data from 2015 to 2024 from the World Development Indicators and Bloomberg. The results show that API Adoption Rate (APIAR) has a positive long-term influence on the Digital Economy Index (DEI), highlighting APIs as a transformative tool that foster innovation, increase scalability within enterprises, and enhance digital transactions in line with SDG 9: Industry, Innovation, and Infrastructure. The findings also indicate that the Number of Active APIs (NAAPIs) exerts a significant and positive effect on DEI in both short- and long-term, which aligns with SDG 8: Decent Work and Economic Growth by fostering accelerated digital transformation and new innovation-driven job opportunities in addition to entrepreneurship via API-driven platforms. API Investment (APII) exhibits a beneficial short-term effect on DEI; nevertheless, it is not significant in the long run, indicating the need for strategic and continuous investment. This finding resonates with SDG 17: Partnerships for the Goals, highlighting the significant role of public–private collaboration in enhancing digital infrastructure and enabling AI solutions. Building on these results, there is an urgent need to improve consistent API ecosystems, enhance collaborative partnerships, and align API strategies to national aspirations for driving Saudi Arabia’s digital economic growth and supporting Vision 2030 and the UN’s SDGs.